ACTIVE OPTIMIZATION OF ROAD SAFETY PARTNERSHIP ACTION (RSPA) BY BEKASI CITY METRO POLICE TRAFFIC UNIT TO SUPPORT THE RESOLUTION OF TRAFFIC AND ROAD TRANSPORTATION PROBLEMS IN THE BEKASI CITY AREA - Ridha Poetera Aditya,; Chairul Muriman Setyabudi, (International Journal of Innovative Technologies in Social Science, 2022)
As a developing country, Indonesia has traffic issues. Bekasi City, which serves as a buffer for Jakarta, is one of the cities experiencing high traffic jams. The Bekasi City Metro Police Traffic Unit cannot solve various traffic challenges and obstacles on its own; synergistic cooperation among stakeholders is required. Bekasi City Metro Police Traffic Unit efforts to reduce various traffic problems in Bekasi City, one of which is undertaken through the Road Safety Partnership Action activity. This research aims to examine the active optimization of the Road Safety Partnership Action by the Bekasi City Metro Police Traffic Unit in addressing traffic and road transportation issues. This study uses a qualitative approach with analytical descriptive to provide a detailed description of the situation that occurred. The data used uses data primary and secondary. Data collection techniques are observation, interviews, and document studies. Evaluation of data reliability and validity through tringulation. The results of the study show that Bekasi City is faced with high traffic problems seen from the large number of traffic violations and accidents. Road Safety Partnership Action activities are still not optimal due to poor planning, organization, implementation and control. Then, when active RSPA is faced with a number of obstacles such as the lack of quality and quantity of human resources, lack of budget support, lack of support for facilities and infrastructure, and the process of agreement regarding the active Road Safety Partnership Action is only understood at the leadership level.